Posters 2019
DOI: 10.1136/gutjnl-2019-bsgabstracts.225
|View full text |Cite
|
Sign up to set email alerts
|

PTU-016 Effectiveness of a nurse-led fibroscan service towards enhanced care in liver disease

Abstract: Discussion Nurse led fibroscan service shows effective monetary benefit in good enhanced care of liver disease . It gives a more accurate diagnosis as compared to USS and also helps in avoiding the invasive liver biopsy in majority of the cases.Utilised in a correct manner it can help in appropriate care of the liver disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the current study, a total of five nurses in rotation handled the complete volume of transient elastography, easing the load on physicians, as was seen in another study (El-Gohary et al, 2018). Other studies found that nurse-led transient elastography managed 90% of patients in primary care, reduced secondary care referrals (Crossan et al, 2019), enhanced liver care delivery (Kendrick et al, 2019;Matthews, MacGilchrist, Coulter-Smith, Jones, & Cetnarskyj, 2019) and uptake of liver services with 67% acceptability (Matthews et al, 2019). By detecting diagnoses early, nurse-led transient elastography also showed monetary benefits (El-Gohary et al, 2018;Kendrick et al, 2019) including cost-effectiveness (El-Gohary et al, 2018) and cost savings (Kendrick et al, 2019).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the current study, a total of five nurses in rotation handled the complete volume of transient elastography, easing the load on physicians, as was seen in another study (El-Gohary et al, 2018). Other studies found that nurse-led transient elastography managed 90% of patients in primary care, reduced secondary care referrals (Crossan et al, 2019), enhanced liver care delivery (Kendrick et al, 2019;Matthews, MacGilchrist, Coulter-Smith, Jones, & Cetnarskyj, 2019) and uptake of liver services with 67% acceptability (Matthews et al, 2019). By detecting diagnoses early, nurse-led transient elastography also showed monetary benefits (El-Gohary et al, 2018;Kendrick et al, 2019) including cost-effectiveness (El-Gohary et al, 2018) and cost savings (Kendrick et al, 2019).…”
Section: Discussionmentioning
confidence: 59%
“…Other studies found that nurse-led transient elastography managed 90% of patients in primary care, reduced secondary care referrals (Crossan et al, 2019), enhanced liver care delivery (Kendrick et al, 2019;Matthews, MacGilchrist, Coulter-Smith, Jones, & Cetnarskyj, 2019) and uptake of liver services with 67% acceptability (Matthews et al, 2019). By detecting diagnoses early, nurse-led transient elastography also showed monetary benefits (El-Gohary et al, 2018;Kendrick et al, 2019) including cost-effectiveness (El-Gohary et al, 2018) and cost savings (Kendrick et al, 2019). Cost savings of more than 40% for the healthcare system was reported by Crossan et al (2019).…”
Section: Discussionmentioning
confidence: 99%